Behavior of RR soybeans subjected to different formulations and rates of glyphosate in the reproductive period - Albrecht,A.J.P. (2014)
Recent studies indicate that glyphosate applied in post-emergence in RR soybean can eventually cause phytotoxic effects. However, there are many questions that need to be clarified in the scientific and technical contexts, involving the issue of RR soybeans regarding the use of glyphosate. This study has assessed the impact of the application of different doses and formulations of glyphosate in the reproductive period of RR soybean (R1 stage). For that purpose, an experiment in the field was conducted in two harvests (2011/12 and 2012/13), in which a 2 x 5 factorial design was used (formulations versus doses) totaling 10 treatments. In these two experiments the variables related to agronomic performance were: phytotoxicity (7, 14, 21 and 28 days after application), plant height, number of pods per plant, yield and weight of 100 grains (end of soy cycle). The results obtained allowed characterizing phytotoxicity and damages to the height and yield in RR soybean, with increasing rates of glyphosate applied in the reproductive period.